RodZ, a key player of the bacterial morphogenic apparatus - Robalino-Espinosa, José Sebastián (Revista de la Facultad de Ciencias Médicas (Quito), 2017)
<span style="color: rgba(0, 0, 0, 0.87); font-family: 'Noto Sans', -apple-system, BlinkMacSystemFont, 'Segoe UI', Roboto, Oxygen-Sans, Ubuntu, Cantarell, 'Helvetica Neue', sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Bacteria display a variety of cell shapes, including straight cylinders, banana-shaped cylinders, spirals and American footballs. Maintenance of cell shape is vital for cell growth and division. The distinct shape of most bacteria is maintained by their peptidoglycan layer (PG). Nowadays, we know how sub-unites of the PG are synthesized within the cell, but how the synthesis of PG is coordinated with cell division and growth remains elusive. The PG is inserted into the periplasm and covalently linked into the cell wall. This process is regulated by the morphogenic apparatus composed of MreBCD, PBP2 and RodA. Recently, RodZ an inner membrane protein has been shown to be part of the morphogenic apparatus. Studies using Escherichia coli and Caulobacter crescentus showed that RodZ has a key role in the morphogenesis of Gram-negative bacteria; however, its functions are still unclear in Gram-positive bacteria.